2018
DOI: 10.1002/ece3.3930
|View full text |Cite
|
Sign up to set email alerts
|

A death in the family: Sea lamprey (Petromyzon marinus) avoidance of confamilial alarm cues diminishes with phylogenetic distance

Abstract: Alarm signals released after predator attack function as reliable public information revealing areas of high risk. The utility of this information can extend beyond species boundaries, benefiting heterospecifics capable of recognizing and responding appropriately to the signal. Nonmutually exclusive hypotheses explaining the acquisition of heterospecific reactivity to cues suggest it could be conserved phylogenetically following its evolution in a common ancestor (a species‐level effect) and/or learned during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 119 publications
(184 reference statements)
5
12
1
Order By: Relevance
“…Given the Agnatha is ancestral to all gnathostomes, and the lack of conservation of alarm cue chemistry at larger phylogenetic distances as evidenced by a lack of response to heterospecific cues from distant vs. close relatives [33,75,76]. The sea lamprey also exhibits declining behavioral response to alarm cues collected from confamilial species of Petromyzontide, but fail to respond to cues from more ancestral (Atlantic hagfish, Myxine glutinosa, Myxinidae, Agnatha) and derived (white sucker, Catastomus commersonii , Catastomidae, Actinopterygii) taxa [40]. Further, the process of Soxhlet extraction at high temperature (70–80°C) for multiple hours does not degrade the reactivity of the extract vs. that derived from grinding and freezing skin [13, Wagner et al, in review].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the Agnatha is ancestral to all gnathostomes, and the lack of conservation of alarm cue chemistry at larger phylogenetic distances as evidenced by a lack of response to heterospecific cues from distant vs. close relatives [33,75,76]. The sea lamprey also exhibits declining behavioral response to alarm cues collected from confamilial species of Petromyzontide, but fail to respond to cues from more ancestral (Atlantic hagfish, Myxine glutinosa, Myxinidae, Agnatha) and derived (white sucker, Catastomus commersonii , Catastomidae, Actinopterygii) taxa [40]. Further, the process of Soxhlet extraction at high temperature (70–80°C) for multiple hours does not degrade the reactivity of the extract vs. that derived from grinding and freezing skin [13, Wagner et al, in review].…”
Section: Discussionmentioning
confidence: 99%
“…In the relatively well-studied Ostariophysan fishes, evidence has accrued to suggest these alarm substances include a variety of water soluble nitrogenous compounds including amino acids and oligopeptides [29,30], hypoxanthine-3-N-oxide and similar compounds containing the nitrogen-oxide functional group of purine-N-oxides [3133], histamine [34], protein, possibly as a carrier molecule [35], and glycosaminoglycan chondroitin [36]. Further, mixtures of odorants are expected to compose each alarm cue, as full behavioral reactivity appears species specific, with partial overlap observed among related species [37,38] including lampreys [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Lamprey and other organisms have been found to be capable of adapting their behaviors based on danger cues sensed in their surrounding environments [27]. Damage-released alarm cues originating from conspecific organisms under distress mark regions as high-risk, and can instigate the animals' alarm responses [28]. Experiments have even shown that certain fish species are able to learn from such odor cues, which are believed to play a role in teaching organisms to recognize new entities as predators.…”
Section: Behavior Adaptation and Learningmentioning
confidence: 99%
“…Fish alarm cues, substances released from damaged tissue that elicit antipredator behaviour in conspecifics (= schreckstoff per von Frisch, 1938 , 1941 ), have been extensively studied (for recent reviews, see Ferrari et al , 2010 ; Wisenden, 2015 ). Alarm cues are suspected to be mixtures of compounds, as cross-reactivity is limited to confamilial species, and behavioural responses tend to diminish with increasing phylogenetic distance between the emitter and receiver species ( Hazlett and McLay, 2005 ; Dalesman et al , 2007 ; Schoeppner and Relyea, 2009 ; Mitchell et al , 2012 ; Hume and Wagner, 2018 ). The compounds that compose the mixture are principally detected by ciliated olfactory sensory neurons (OSNs) that stimulate the medial olfactory tract, inducing avoidance or other antipredator responses ( Hamdani and Døving, 2002 , 2007 ; Døving and Lastein, 2009 ).…”
Section: Introductionmentioning
confidence: 99%